An Unusual Cause of Breast Lump: Isolated Tuberculosis of the Breast - Pal, Partha (The American Society of Tropical Medicine and Hygiene, 2014)
A 60-year-old woman presented with a painful lump of 4 months duration in her right breast. She denied any history of breast trauma or family history of breast cancer. Physical examination detected a firm, tender mass in the upper inner quadrant of her right breast without an associated sinus tract. Cytology from fine-needle aspiration of the swelling showed epithelioid cells, lymphohistocytic aggregates, and necrosis. Diagnosis was confirmed by the identification of acid-fast bacilli in tissue sections using Ziehl-Neelsen staining.